Key Questions to Inform National Biodiversity Conservation Policies in Costa Rica - Herrera-Fernández, Bernal (2025)
[Introduction]: Research is critical to formulate new policies and practices that reverse biodiversity losses to date. Prioritizing is also critical for national and international agencies when making investment decisions. [Objective]: Identify and prioritize 40 research questions whose answers contribute to the formulation and implementation of public policies regarding biodiversity conservation, management, and restoration in terrestrial, freshwater, and marine systems in Costa Rica. [Methods]: The process consisted of 3 phases. In the first, an online survey was distributed to 436 participants about research priorities necessary for formulating and implementing national biodiversity public policy. In the second phase, responses were discussed at a national workshop, where participants prioritized the questions. Finally, the workshop results were ranked using the selection criteria to achieve the final research questions. [Results]: The online survey generated 642 research questions, and the national workshop participants prioritized them using the selection criteria to arrive at the final 40. The selected questions cover the following thematic areas: i) ecosystem structure and function; ii) populations and species; iii) protected areas and other conserved areas; iv) global change; v) effectiveness of conservation strategies; vi) human impacts, and vii) impacts of participation and governance.  [Conclusions]: These questions support research funding decisions by institutional authorities, national and international organizations, and civil society organizations. They are also expected to increase the impact on the formulation of new policies and the application of existing ones.